Catalysts by the meter: rapid screening approach of N-heterocyclic carbene ligand based catalysts - Lang, Carolin; Gaertner, Ute; Trapp, Oliver (Chemical communications, 2011)
Here, we demonstrate a versatile screening platform for NHC ligand based catalysts by coating fused-silica micro capillaries with a bonded 1,3-bismesityl-2-imidazolidinylidene ligand. Such micro capillaries can be efficiently converted into (pre)-catalysts from various organometallic precursors by solid-phase chemistry techniques and can be quantitatively screened using on-column reaction chromatography.